2020
DOI: 10.3390/pharmaceutics12121165
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin-Loaded PLGA Nanoparticles for Cancer Therapy: Molecular Weight Effect of PLGA in Doxorubicin Release for Controlling Immunogenic Cell Death

Abstract: Direct local delivery of immunogenic cell death (ICD) inducers to a tumor site is an attractive approach for leading ICD effectively, due to enabling the concentrated delivery of ICD inducers to the tumor site. Herein, we prepared doxorubicin (DOX)-loaded poly(lactic-co-glycolic acid) (PLGA) nanoparticles (NPs) using different molecular weight PLGA (7000 g/mol and 12,000 g/mol), showing different drug release kinetics. The different release kinetics of DOX might differently stimulate a tumor cell-specific immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 32 publications
0
19
0
1
Order By: Relevance
“…In recent years, with the discovery of tumor immune checkpoint molecules, such as cytotoxic T lymphocyte (CTL)-associated protein-4 (CTLA-4), programmed cell death protein-1 (PD-1), and its ligand PD-L1, important breakthroughs have been made in the study of antitumor immune mechanisms, and immunotherapy has become a promising tumor treatment (17,18). Currently, the main strategies in cancer immunotherapy include tumor vaccines, adoptive cellular immunotherapy (ACI), and immune checkpoint blockade (ICB) therapy (19)(20)(21). However, immune drugs alone are not effective for all patients.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the discovery of tumor immune checkpoint molecules, such as cytotoxic T lymphocyte (CTL)-associated protein-4 (CTLA-4), programmed cell death protein-1 (PD-1), and its ligand PD-L1, important breakthroughs have been made in the study of antitumor immune mechanisms, and immunotherapy has become a promising tumor treatment (17,18). Currently, the main strategies in cancer immunotherapy include tumor vaccines, adoptive cellular immunotherapy (ACI), and immune checkpoint blockade (ICB) therapy (19)(20)(21). However, immune drugs alone are not effective for all patients.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmaceutics, regardless of their molar weight, can be loaded into PLGA drug delivery systems and consequently released from the matrix in a controlled manner. Consequently, a wide variety of active compounds can be used as payload of PLGA based drug delivery systems ranging from small molecules such as anti-tumour drugs with molar weight 0.5 kDa [ 15 ] to proteins and enzymes with molar mass up to 50 kDa [ 16 , 17 ]. The drug release profile of PLGA based drug delivery systems is usually characterized by the initial burst of a loaded drug followed by zero order kinetics release [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it has been shown that low molecular weight PLGA nanoparticles release the payload at a higher rate ( 76 78 ). Therefore, the molecular weight can influence how long a drug of interest is released and exposed to the area of interest ( 77 , 78 ). These previous studies support our data showing that the low molecular weight releases the payload after 5 days.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the low molecular weight, 5-10 kDa, released the plasmid quickly, the nanoparticles were unstable in saline, a common liquid vehicle used for intravenous drug delivery (68,(72)(73)(74)(75). Similarly, it has been shown that low molecular weight PLGA nanoparticles release the payload at a higher rate (76)(77)(78). Therefore, the molecular weight can influence how long a drug of interest is released and exposed to the area of interest (77,78).…”
Section: Discussionmentioning
confidence: 99%